Compositional and Functional Comparisons of the Microbiota in the Colostrum and Mature Milk of Dairy Goats - Zhannur Niyazbekova; Xiao-Ting Yao; Ming-Jie Liu; Nomin Bold; Juan-Zhen Tong; Jian-Jun Chang; Ying Wen; Li Li; Yong Wang; De-Kun Chen; Wen-Tao Ma (Animals, 2020)
Goat milk is essential for the initial development of kids by providing a great source of commensal bacteria. In this study, we analyzed the microbiota of the milk of 30 healthy Saanen dairy goats. The 30 samples comprised 15 colostrum and 15 mature milk samples, collected from three different farms of Shaanxi Province. Colostrum samples were collected daily for five days post-delivery and mature milk was collected on the 7th, 10th, 20th, 30th, and 40th days. The result showed that microbial alpha diversity was higher in the mature milk compared with that in the colostrum. Linear discriminant analysis effect size (LEfSe) was performed to detect differentially abundant taxa in colostrum and goat milk. According to taxonomy results, Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes were the predominant bacteria phyla in both colostrum and mature milk. In addition, lactation stage noticeably influenced the composition of milk microbiota. Specifically, Novosphingobium, Brachybacterium, Psychrobacter, Lactobacillus, Yersinia, Roseateles, Rothia, Sanguibacter, Cloacibacterium, Variovorax, Sphingobacterium, and Coxiella were enriched in the colostrum, while Georgenia, Peptostreptococcus, Bacteroidales, Yaniella, Planomicrobium, Cloacibacterium, Azospirillum, Turicibacter, Cupriavidus, Herbaspirillum, Rhodobacteraceae, and Aeromonadales were the dominant genera in the mature milk. The enriched metabolic functions of the goat milk microbiota were predicted by PICRUSt and classified by KEGG pathway. Moreover, the abundances of environmental information processing, cellular processes pathway, genetic information processing pathway, organismal systems pathway, and metabolism pathway were significantly different between microbiota of colostrum and mature milk. Altogether, our study disclosed the significant difference between the microbial communities of colostrum and mature milk and provided grounds for further research in dairy microbiology.